Chloramphenicol and tetracycline decrease motility and increase invasion and attachment gene expression in specific isolates of multidrug-resistant Salmonella enterica serovar Typhimurium - Brunelle, Brian W.; Bearson, Bradley L.; Bearson, Shawn M. D. (Frontiers in Microbiology, 2015)
Salmonella enterica serovar Typhimurium is one of the most common serovars isolated from humans and livestock, and over 35% of these isolates are resistant to three or more antibiotics. Multidrug-resistant (MDR) Salmonella is a public health concern as it is associated with increased morbidity in patients compared to antibiotic sensitive strains, though it is unknown how the antibiotic resistant isolates lead to a more severe infection. Cellular invasion is temporally regulated in Salmonella and normally occurs during late-log and stationary growth. However, our previous work determined that a 30 minute exposure to a sub-inhibitory concentration of tetracycline can induce the full invasion phenotype during early-log growth in certain MDR S. Typhimurium isolates. The current study examined whether sub-inhibitory concentrations of other antibiotics could also induce the invasiveness in the same set of isolates. Ampicillin and streptomycin had no effect on invasion, but certain concentrations of chloramphenicol were found to induce invasion in a subset of isolates. Two of the isolates induced by chloramphenicol were also inducible by tetracycline. RNA-seq analyses demonstrated that chloramphenicol and tetracycline both down-regulated motility gene expression, while up-regulating genes associated with attachment, invasion, and intracellular survival. Eleven fimbrial operons were up-regulated, which is notable as only three fimbrial operons were thought to be inducible in culture; six of these up-regulated operons have been reported to play a role in Salmonella persistence in mice. Overall, these data show that the normal progression of the genetic pathways that regulate invasion can be expedited to occur within 30 minutes due to antibiotic exposure. This altered invasion process due to antibiotics may play a role in the increased intensity and duration of infection observed in patients with MDR Salmonella.